Reasoning Criminal – Implikasi Limbah Hasil Operasional Kapal Terhadap Ekosistem Laut di Selat Malaka - Verdinand Robertua; Bryan Libertho Karyoprawiro (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
The Malacca Strait, which has always been the most strategic world trade route. The majority of foreign vessels crossing the Malacca Strait transit at the Port of Singapore. The potential of environmental pollution in the Malacca Strait area is also very large, especially the pollution from vessel waste resulting from the operational activities of vessels in the form of liquid waste and garbage dumped in vain and the washing of vessels illegally. The operational activities of foreign ships in violation of international treaties and Indonesian law often occur in Indonesian coastal areas. Indonesian waters were victims of foreign vessels who carried out illegal activities in order to reduce operational costs and avoid sanctions from the port authorities and the Singapore's sincerity which required that every vessel to be anchored in Singapore's port was clean from waste. Regulations made by the Singapore Government encourage illegal ship laundering and waste disposal in the Straits of Malacca. The supervision of severe penalties against each vessel that crosses and violates the rules, and the establishment of a special zone of vessel cleaning in the Straits of Malacca can reduce environmental damage. This research uses qualitative methods using rational choice and institutional approach in environmental view to see how environmental problems caused by vessel waste occurred and cause cross border problems threatening ecosystem in the Straits of Malacca, especially the Indonesian water area. Data used in the form of qualitative data are collected through document studies, interviews, document analysis, focused discussions, and observations made.